Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1177/0956462415584466
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of cervical squamous intraepithelial lesions among HIV-infected women in Dar es Salaam, Tanzania

Abstract: To determine the prevalence and predictors of cervical squamous intraepithelial lesions (SIL) among HIV-infected women in Tanzania, a cross-sectional study was conducted among HIV-infected women at HIV care and treatment clinics. A Papanicolaou (Pap) smear was used as a screening tool for detection of cervical SIL. From December 2006 to August 2009, 1365 HIV-infected women received cervical screening. The median age was 35 (interquartile range [IQR]: 30-42) years, and the median CD4 + cell count was 164 (IQR: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 27 publications
(37 reference statements)
2
17
4
Order By: Relevance
“…However, the finding is in contrast to the reports of Liu et al (2016) in Tanzanian and Ononogbu et al (2013) in Abuja, Nigeria who found a significant association between increasing age and the risk of developing premalignant lesions of the cervix among the women.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…However, the finding is in contrast to the reports of Liu et al (2016) in Tanzanian and Ononogbu et al (2013) in Abuja, Nigeria who found a significant association between increasing age and the risk of developing premalignant lesions of the cervix among the women.…”
Section: Discussioncontrasting
confidence: 56%
“…But in contrast, Liu et al (2016) in their study of 1365 Tanzanian HIV positive women who had cervical cancer screening, reported that age more than 50 years was significantly associated with the occurrence of cervical cytological abnormalities. Similarly, Ononogbu et al (2013) studied 2501 HIV positive women in Abuja, Nigeria and reported that increasing age and age >40 years were associated with reduced risk of developing premalignant lesions of the cervix among the women.…”
Section: Introductionmentioning
confidence: 90%
“…One publication provided data from two countries, 17 and was considered as two individual studies in the analysis. 12 further studies reported the association of ART with the prevalence of combined cytology diagnosed outcomes of atypical squamous cells of undetermined significance (or higher), 42 , 43 , 44 , 45 , 46 , 47 , 48 and low-grade SIL (or higher), 49 histology diagnosed CIN (grade 1 or higher), 50 , 51 and abnormalities on visual inspection with colposcopy ( appendix p 20 ). 52 , 53 …”
Section: Resultsmentioning
confidence: 99%
“…Although HPV infection is the major cause of cervical cancer, several studies in the past have implicated cigarette smoking as a cofactor for cervical cancer in both HIV-infected and uninfected women 51 , 52 . Moreover, most of the recent studies have emphasized HPV infection, immunosuppression by HIV, age, abortion, and vaginal abnormalities as major risk factors for cervical cancer in HIV-infected women 50 , 53 55 . Only a few recent reports associate smoking with cervical cancer risk in HIV-infected women.…”
Section: Cervical Cancermentioning
confidence: 99%